Gamification Appeal and Customer Engagement Increase Online Consumer Repurchase Intentions - Elsya Tri Hasanah; Mila Widia Putri; Siska Ernawati Fatimah (Universitas KH. Abdul Chalim Mojokerto, 2025)
Gamification with the use of non-gaming through points, levels, challenges, rewards, or leaderboards on e-commerce shopping platforms becomes a more interesting activity and motivates customer engagement. This study aims to explore the factors that influence repurchase intention in e-ecommerce, with a focus on gamification and customer engagement. The participants in this study were individuals from Cirebon City, aged between 15-29 years old, with a sample size of 399 respondents determined using the Slovin formula. The sampling technique used was purposive random sampling. The research data were analyzed using the SEM-PLS (Partial Least-Structural Equation Modeling) method. The research findings reveal that gamification and customer engagement significantly influence Generation Z's intention to repurchase in e-commerce. Gamification strongly drives Generation Z's purchase intention in e-commerce shopping, this is because gamification creates a fun and interactive shopping experience. An interactive gamification strategy can be utilized by e-commerce businesses to encourage Generation Z's buying interest, so that the strategy created is interesting and effective to be of interest to Generation Z, which will increase consumer buying interest.